Determinants of transfer pricing decisions in Indonesia manufacturing companies - Anisa Susanti; Amrie Firmansyah (Jurnal Akuntansi dan Auditing Indonesia, 2018)
This research aims to investigate tax expenses, tunneling, and bonus on transfer pricing decisions in Indonesia. The practice of transfer pricing as one form of tax avoidance may threaten state revenues. This research is quantitative research with multiple linear regression models with panel data. The samples used in this research are manufacturing companies listed on the Indonesia Stock Exchange (IDX). The type of data used in this study is secondary data in the form of financial statements of companies listed on IDX from 2011 to 2015. The samples are selected using a purposive sampling method with the number of samples of 50 companies. The results suggest that tax expenses and tunneling are negatively associated with transfer pricing decisions while the bonus is not associated with transfer pricing decisions.